Dietary Adherence in Children with Amino Acid Metabolism Disorders and its Impact on Caregivers’ Quality of Life - Yong, Chien Yin; Rajikan, Roslee; Lim, Jing Ying; Yahya, Hanis Mastura; Ghazali, Shazli Ezzat; Leong, Huey Yin; Mohamad, Maslina; Md. Rani, Rufaidah; Mohd Fahmi Teng, Nur Islami (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This study explored the relationship among socio-demographic factors, patients’ dietary adherence, and the Quality of Life (QoL) experienced by their caregivers. A cross-sectional study was carried out, involving 66 caregivers of pediatric patients in Malaysia diagnosed Amino Acid Metabolism Disorders (AAMDs). Dietary adherence was assessed using a modified version of the Malaysia Medication Adherence Assessment Tool (MyMAAT-12), and the caregiver’s QoL was evaluated using the 36-Item Short Form Survey (SF 36) questionnaire. Majority of the patients were Malay (75.76%), and female (59.1%). Statistical analysis found that caregivers with a higher education level were associated with a higher dietary adherence (rs (64)=0.382, p=0.002) and better mental health (rs (64)=0.281, p=0.022). The age of patients had negative significant correlation with the physical function and general health (rs (64)=0.287, p=0.019) of their caregivers. Besides that, dietary adherence was negatively correlated with social functioning (p=0.010), role limited due to physical health (p=0.018), role limited due to emotional problems (p=0.022), vitality (p=0.021), mental health (p=0.014) and pain (p=0.011). Conclusion: Dietary adherence had a significant impact on the QoL for caregivers of patients with amino acid metabolism disorders. Therefore, it is crucial to explore appropriate treatment strategies and provide support to enhance patients' adherence to their dietary requirements, simultaneously improving the caregivers' QoL.